Studies of Formation and Content of the Term ‘Logistics Activities’: Theoretical Aspects - Ivanova, M.І. (Економічний вісник Донбасу, 2015)
The investigation of theoretical aspects of formation and content of the term ‘logistics activities’ allowed clarifying the goals, objectives, objects, subjects and components of logistics activities. The paper has shown a system decomposition of the logistics activities at an industrial enterprise and the author’s definition of the term ‘logistics activities’.